Effect of breeding season on fertility of sheep following estrus synchronization and fixed-time artificial insemination under field conditions in semi-arid tropical region. Issue 5 (2nd September 2016) - De, Kalyan; Kumar, Davendra; Balaganur, Krishnappa; Gulyani, Rajeev; Naqvi, S. M. K.
Abstract: Accelerated lambing system is heavily reliant on reproductive technologies meant to enable off the season breeding in sheep. Therefore, the present study was programmed to assess the effect of breeding season (BS) on fertility of sheep following estrus synchronization (ES) and fixed time artificial insemination (FTAI). A total of 248 and 365 ewes were synchronized and inseminated during the BS (Febuary–March and July–September) and non-breeding season (NBS) respectively, during 2012–14. Synchronization of estrus was done by AVIKESIL-S, intra-vaginal progesterone sponges kept in situ in vagina for 12 days. 200 IU eCG was administered intramuscularly on 12th day after sponge withdrawal. FTAI was performed twice in ewes exhibiting signs of estrus at 48 and 56h after sponge removal, using liquid chilled semen of Patanwadi/Malpura rams containing 100 million sperm. Breeding season had no significant ( p <0.05) effect on estrus synchronization. The estrous responses during the BS and NBS were 84.68% and 83.29% respectively. The lambing percentage during BS was 66.67%, which is significantly ( p <0.05) higher than the lambing percentage of NBS (57.57%). Although, the lambing percentage in NBS maneuvered ewes were lower than the BS ewes but still the technology can be used to offset the effect of anestrus and to augment production in sheep.